Application practice of base station inspection based on AI - Feng ZHOU; Bing WANG (Dianxin kexue)
Since the traditional base station inspection of telecom operators is enforced manually now,it not only consumes manpower,but also has many problems,such as safety,unverifiable result,and incomplete information and so on.The application practice and challenge of artificial intelligence technology in base station routine inspection of operators was introduced,which included the general situation of intelligent patrol technology and industry development,the demand of traditional patrol to intelligent transformation,intelligent patrol solutions,effect evaluation and data analysis,etc.On this basis,the application scenarios and service modes of future AI automatic patrol for telecom operators were discussed,and the deployment scheme of intelligent patrol platform was proposed.